The Effect of Surface Wettability and Coalescence Dynamics in Catalytic Performance and Catalyst Preparation: A Review. Issue 6 (27th February 2019) - Li, Tao; Wang, Junjun; Wang, Fenglong; Zhang, Lishu; Jiang, Yanyan; Arandiyan, Hamidreza; Li, Hui
Abstract: The interactions between the reactants and catalysts surfaces play a significant role in heterogeneous catalysis, thus to tune the interfacial properties between them has emerged as an important topic. This review has summarised some recent advances about the effects of wettability on the catalytic reactions, including hydrophilicity, hydrophobicity, and dewetting properties. In addition, the effect of coalescence dynamics among the catalyst particles is also discussed based on a series of investigations. Although the researchers have realised the importance of wettability, the ability to tune the wettability in their work needs to be further enhanced. Therefore, we finally highlighted considerable useful approaches to achieve controllable wettability and coalescence. It is expected that in the future design of catalysts, researchers should pay more attention to tuning the interfacial structure to achieve the enhanced catalysts behaviours. Abstract : Wet wet wet : Surface wettability and coalescence dynamics have a great impact on the catalyst activity and the preparation of catalyst, and the catalytic performances could be significantly improved by the fine control of surface wettability and coalescence dynamics. Here, the authors provide many effective approaches to achieve the controllable surface wettability and coalescence, which is expected to be applied in the catalytic field.